Minding the Gap Between Perceived and Projected Destination Image by Using Information and Communication Platforms and Software - Briciu, Victor Alexandru; Nechita, Florin; Demeter, Robert; Kavoura, Androniki (IGI Global, 2019)
The article examines a double case study framework for analyzing perceived and projected destinations by using ITC solutions. First, 22,362 photos tagged with “Brasov” were collected and analyzed using the Flickr API. Second, a descriptive-explanatory research was employed, applying an instrument for the analysis and to address the online identity of place brands where a proposed online platform generates an automatic score calculation. The spatial patterns of tourist activity revealed many similarities and differences compared to promoted attractions by the DMOs, as the results indicated that geotagged photos reflect the projected image of the destination as the data provided a hotspot distribution of popular tourist attractions. The article makes a theoretical and practical contribution: (a) visual imagery may be more fully implemented in research studies; and (b) the distribution of popular tourist attractions may be in synergy between the perceived and projected image of a destination. Implications for marketing managers are presented.
Keywords: Brasov; destination image; identity characteristics; IT&C applications; place brands; tourism websites; Transylvania; visitor generated visual content; visual data analysis